Effect of Ultraviolet Photofunctionalization on implant stability and osseointegration: a randomized controlled trial of UVA and UVC on SLA-Coated Titanium implant - Zaheer, Naauman; Shahbaz, Maliha; Zaheer, Usman; Ahmad Rajion, Zainul; Zaigham, Abdul Moeed; Saeed, Muhammad Qasim (Khyber Medical University, 2024)
OBJECTIVES: To evaluate the effect of ultraviolet A (UVA) and ultraviolet C (UVC) irradiation on sandblasted, large-grit, acid-etched (SLA) coated titanium implants by measuring their impact on implant stability and osseointegration in the surrounding bone. METHODS: This interventional experimental study was conducted jointly by CMH Lahore Medical College and Universiti Sains Malaysia from July 2017 to December 2018, with ethical approval obtained from both institutions. Sixty-six SLA-coated titanium implants (10 mm length, 4.5 mm width) were placed in partially edentulous patients aged >20 years, randomized into three groups: Group A (control, untreated implants), Group B (implants irradiated with UVA), and Group C (implants irradiated with UVC). Implant stability quotient (ISQ) and osseointegration speed index (OSI) were measured using the Ostell Mentor device at baseline (day 0), the 8 week, and after 26 weeks of functional loading. Statistical analysis included linear regression and t-tests. RESULTS: Baseline ISQ levels were 62.1, 65.2, and 69.3 for Groups A, B, and C, respectively. At the 8th week, ISQ levels increased significantly to 77.0, 81.5, and 82.5. Group B (UVA) demonstrated the highest OSI (8.5±3.3), with significant ISQ improvement compared to the control group (p=0.009). UVC irradiation (Group C) showed no statistically significant difference in ISQ compared to the control group (p=0.191). Patients with lower baseline ISQ showed greater improvement across all groups. CONCLUSION: Photofunctionalization with UVA significantly enhanced implant stability and osseointegration, suggesting its potential for improving clinical outcomes in dental implantology. Further research is needed to explore the long-term effects of UVC irradiation.Clinical Trial Registration Number: NCT05467488